Studi Evaluasi Potensi Eco-Nature Tourism & Eco-Culture Tourism di Kawasan Ekowisata Sungsang, Kabupaten Banyuasin - Adam Rachmatullah; Oktovianus Oktovianus; Hanni Adriani (Universitas Pendidikan Ganesha, 2022)
One of the efforts in measuring the amount of ecotourism potential is by conducting a series of academic processes in the form of inventory and assessment of ecotourism potential or better known as ecotourism assessment. The Ecotourism Potential Evaluation method used is the theory of Avenzora (2008) to distinguish 7 assessment criteria for each element of ecotourism potential, which is then analyzed using the One Score One Criteria System method. The results of the study show that the Sungsang Ecotourism Area has a relatively high potential for eco-nature tourism and eco-culture tourism; both in terms of the potential for natural phenomena, flora and fauna, as well as material & immaterial heritage. The results of field studies prove that the various eco-nature tourism owned by the Sungsang Ecotourism Area is classified as relatively high (score 5); while eco-culture tourism is producing a score of 6 or high meaning. There are at least 4 syntheses that can be done in the future: 1) The plan for utilization of ecotourism resources that must be able to avoid the occurrence of over-supply dynamics in the ecotourism supply process; 2) The plan to utilize the diversity of ecotourism resources that should not cause over-exploration or over-exploitation of germplasm or ecosystems; 3) The need for study and application of the carrying capacity of recreation / tourism sites and the carrying capacity of recreation/ tourism destinations; 4) A more comprehensive, systematic and objective study is needed which is mapped and outlined in the Grand Design Document or Ecotourism Master Plan).